Pharmacological management of relapsed/refractory NSCLC with chemical drugs. (11th February 2017) - Karachaliou, Niki; Sosa, Aaron E.; Barron, Feliciano Barron; Gonzalez Cao, Maria; Santarpia, Mariacarmela; Rosell, Rafael
ABSTRACT: Introduction : Lung cancer is the leading cause of cancer death in both genders. In the early stages the disease is asymptomatic and most patients appear with metastasis at the time of the diagnosis. The discovery of key oncogenic events mainly in lung adenocarcinoma, like EGFR mutations or ALK rearrangements has changed the treatment landscape and has improved the prognosis of lung cancer patients. Inevitably, all patients initially treated with either chemotherapy or targeted therapies develop resistance and require a second-line therapeutic approach. Areas covered : In this review we are discussing the current treatment of relapsed or refractory lung cancer. We have thoroughly searched the literature (Pubmed) the last five years for studies or reviews published on the issue of second-line therapy in lung cancer using as key words, lung cancer, relapse, EGFR mutations, ALK rearrangements, chemotherapy and immunotherapy Expert opinion : The prognosis of lung cancer has been radically improved. Due to the recent development of checkpoint inhibitors, this also occurs for patients whose tumor's are not driven by a genetic alteration and who, until recently, derived only minimal benefit from chemotherapy.